2012
DOI: 10.1117/1.jbo.17.9.096016
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and photoacoustic characterization of micron-sized perfluorocarbon emulsions

Abstract: Abstract. Perfluorocarbon droplets containing nanoparticles (NPs) have recently been investigated as theranostic and dual-mode contrast agents. These droplets can be vaporized via laser irradiation or used as photoacoustic contrast agents below the vaporization threshold. This study investigates the photoacoustic mechanism of NPloaded droplets using photoacoustic frequencies between 100 and 1000 MHz, where distinct spectral features are observed that are related to the droplet composition. The measured photoac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…Previously our research group has shown that photoacoustic frequencies above 100 MHz can be used to identify and size spherically symmetric nanoparticle-loaded micron-sized perfluorocarbon droplets [15]. Periodically varying minima and maxima were observed throughout the power spectrum that are unique to the size, shape and composition of the object.…”
Section: Discussionmentioning
confidence: 97%
“…Previously our research group has shown that photoacoustic frequencies above 100 MHz can be used to identify and size spherically symmetric nanoparticle-loaded micron-sized perfluorocarbon droplets [15]. Periodically varying minima and maxima were observed throughout the power spectrum that are unique to the size, shape and composition of the object.…”
Section: Discussionmentioning
confidence: 97%
“…However, the small size also allows for increased tumor penetration and interaction with biomolecules. Besides plasmonic nanoparticles and dyes, many other types of agents have been considered and tested for photoacoustic imaging including carbon nanotubes (39), nanodroplets (40,41), and liposomes and polymer (36) particles. For more and frequency) data can be extracted, allowing more precise image quantification.…”
Section: Photoacoustic Imaging Instrumentationmentioning
confidence: 99%
“…They are more resistant to ultrasonic waves than monomolecular layers of lipids or surfactants 20,21 ; they can also act as a drug carrier and ligand for targeted imaging or targeted drug delivery 22 . Poly(Llactide-co-glycolide) (PLGA) is one of the most used synthetic biodegradable polymers in the drug delivery system 7,8,19 , and is approved for clinical application 23 .…”
Section: Introductionmentioning
confidence: 99%